2019
DOI: 10.1007/s00018-019-03332-w
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenic acid and cancer: facts and controversies

Abstract: Kynurenic acid (KYNA) is an endogenous tryptophan metabolite exerting neuroprotective and anticonvulsant properties in the brain. However, its importance on the periphery is still not fully elucidated. KYNA is produced endogenously in various types of peripheral cells, tissues and by gastrointestinal microbiota. Furthermore, it was found in several products of daily human diet and its absorption in the digestive tract was evidenced. More recent studies were focused on the potential role of KYNA in carcinogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
85
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 118 publications
(217 reference statements)
0
85
0
Order By: Relevance
“…Several studies report alterations in the concentration of KYNA and the expression of GPR35 in different cancers. Increased levels of KYNA have been detected in colon carcinoma, oral squamous cell carcinoma, non-small cell lung carcinoma and multiple myeloma, whereas a reduced concentration of this metabolite was observed in renal cell carcinoma and primary cervical cancer [122]. In parallel, and in comparison to paired normal tissues, the expression of GPR35 was reduced in prostate, testicular and thyroid tumors; increased in stomach, pancreatic, colon and non-small-cell lung cancer, and unaltered in breast and ovarian cancer [122].…”
Section: G-protein-coupled Receptor 35 (Gpr35)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies report alterations in the concentration of KYNA and the expression of GPR35 in different cancers. Increased levels of KYNA have been detected in colon carcinoma, oral squamous cell carcinoma, non-small cell lung carcinoma and multiple myeloma, whereas a reduced concentration of this metabolite was observed in renal cell carcinoma and primary cervical cancer [122]. In parallel, and in comparison to paired normal tissues, the expression of GPR35 was reduced in prostate, testicular and thyroid tumors; increased in stomach, pancreatic, colon and non-small-cell lung cancer, and unaltered in breast and ovarian cancer [122].…”
Section: G-protein-coupled Receptor 35 (Gpr35)mentioning
confidence: 99%
“…Increased levels of KYNA have been detected in colon carcinoma, oral squamous cell carcinoma, non-small cell lung carcinoma and multiple myeloma, whereas a reduced concentration of this metabolite was observed in renal cell carcinoma and primary cervical cancer [122]. In parallel, and in comparison to paired normal tissues, the expression of GPR35 was reduced in prostate, testicular and thyroid tumors; increased in stomach, pancreatic, colon and non-small-cell lung cancer, and unaltered in breast and ovarian cancer [122]. Functionally, GPR35 signaling pathway via ERK kinase has been involved in several cellular processes such as proliferation, cell survival and even metastasis [123], and overexpression of GPR35 seems to confer drug resistance in non-small-cell lung cancer through β-arrestin-2/Akt signaling [124].…”
Section: G-protein-coupled Receptor 35 (Gpr35)mentioning
confidence: 99%
“…This compound is synthesized in the reaction of kynurenine transamination, which is catalyzed by kynurenine aminotransferases (KATs). KYNA exhibits pro-healthy properties, due to its antioxidant, anti-inflammatory and anticonvulsant action [7][8][9]. It was also reported that KYNA can have protective properties on the human brain [9] and an inhibitory effect on the proliferation of colon cancer cells (i.e., adenocarcinoma HT-29 cells) [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is an antioxidant and neuroprotective compound [ 10 ]; in particular, altered KYNA levels may suggest an inflammatory response, as shown in Alzheimer’s disease patients [ 11 ]. KYNA reduces the heart rate and glaucoma in mice and it has a role in carcinogenesis and cancer therapy [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%